Ultrasound findings in knee of patients of osteoarthritis and their correlation with pain - Rath, Prasan Deep; Pandey, Swetal Chandraprakash (International Journal of Research in Orthopaedics, 2019)
Background: Osteoarthritis (OA) is a common joint disorder, with the knee being one of the most frequently involved sites. Conventional radiography (CR), hitherto the primary imaging tool in OA, shows late and indirect findings. Ultrasound (US), on the other hand, offers the possibility to depict different structures within the knee. The main objectives of this study is to asses correlation of Ultrasonography (USG) findings of OA knees and pain assessed in each knee using a numerical rating scale (NRS) from 0 to 10. Methods: This study was a single center cross sectional observational study. Patients presenting to rheumatology clinic between February 2017 to March 2017 and satisfying ACR clinical criteria for osteoarthritis of knees were taken. Pain assessed in each knee using NRS. USG evaluation of painful knee was done using standard protocols. Results: In this study, 9 patients and 17 knees were examined. The mean age was 65.7 yrs with more females (66%) as compared to males (33.3%), mean disease duration was 6 yrs with majority of patients (88%) on pain reliever medications (NSAIDS). Ultrasound showed that synovitis and osteophytes has negative correlation with pain score (r=-0.06, r-.09). Presence of cartilage loss had slightly higher correlation with pain score (r=0.18). The meniscal protrusion (r value 0.15) is associated slight correlation with pain score. Conclusions: Ultrasound can assess many soft tissue pathologies which cannot be seen on conventional radiography, however the importance of these soft tissue pathologies is uncertain and remains to be determined. In this study we could not find any significant correlation between pain and ultrasound findings.